PERILAKU IBU DALAM PEMBERIAN TERAPI JERUK NIPIS DAN KECAP MANIS / MADU PADA ANAK (1-5 TAHUN) - mega, Megawati; Retnoningrum, Dyah (JURNAL SMART ANKes, 2024)
ISPA that is not handled properly can cause more serious complications. One of the most common and dangerous complications of ISPA I is pneumonia. Pneumonia can cause death, especially in toddlers among other ISPA diseases, which is around 80- 90%. HO recommends the use of traditional medicines including herbs in maintaining public health, and prevention and treatment of disease, especially for chronic diseases and cancer. Making lime as a drink can also be used as a natural remedy for mild coughs and colds (Zulfahmi et al, 2020). Sweet soy sauce or honey mixed with lime juice can be used to relieve coughs and soothe the throa. Research Objectives: To determine the relationship between knowledge, family support, and access to information with the behavior of mothers giving lime and sweet soy sauce/honey to children (1-5 years) with a mild cough at the MTBS Polyclinic at the Gerunggang Health Center. Research Methods: quantitative research with a cross-sectional approach and survey methods through questionnaires. This research was conducted from January to March 2023. The population in this study were mothers whose children (1-5 years) were treated for mild coughs at the MTBS Poly Clinic at the Gerunggang Health Center, a total of 128 people. Research sample that taken as many as 80 respondents. Research Results: The results of this study all show that there is a significant relationship between the independent and dependent variables, namely Knowledge p- value = 0.007 <? (0.05), Family support p-value = 0.001 <? (0.05) and Access to information p-value = 0.001 < ? (0.05). Conclusion: Respondents who gave lime and sweet soy sauce/honey to children (1-5 years) had mild coughs as many as 55 people (68.8%) less than those who did not. There is a significant relationship between Knowledge, Family Support, and Access to Information with the behavior of mothers giving lime and sweet soy sauce/honey to children (1-5 years) with a mild cough at the MTBS Polyclinic at the Gerunggang Health Center in 2023. Keywords: Access to Information, amily support, ISPA, Knowledge, Mother's behavior